Utilization of healthcare services among children members of Medical Insurance for a New Generation Utilización de servicios de atención a la salud en niños afiliados al Seguro Médico para una Nueva Generación - Ricardo Pérez-Cuevas; Svetlana V Doubova; Sergio Flores-Hernández; Onofre Muñoz-Hernández (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To describe the utilization and associated factors for preventive and curative care utilization among children affiliated to the Medical Insurance for a New Generation (SMNG). MATERIALS AND METHODS: Data from the 2009 National Survey of SMNG was analyzed. RESULTS: The analysis represented 1 316 867 children; 25% of urban and 37.5% of rural mothers that took their children to well-child visits. Covariates associated with preventive care utilization were children <12 months, low-birth weight, history of infectious or other diseases, mother >35 years, mother's literacy level of bachelor degree, housewife, attendance at >7 antenatal care visits, and living in a rural area. Curative care: 12% attended emergency room services, 5.4% were hospitalized and 66% received ambulatory care. Covariates associated with curative care utilization: child history of frequent diseases, mother living with husband/partner, mother's literacy level of bachelor degree, attendance >7 antenatal care visits and having paid work. CONCLUSION: It is needed to reinforce the programs encouraging mothers to seek preventive care regularly. OBJETIVO: Describir el uso y factores asociados para la atención preventiva y curativa de niños afiliados al Seguro Médico para una Nueva Generación (SMNG). MATERIAL Y MÉTODOS: Análisis de la información de la Encuesta Nacional SMNG 2009. RESULTADOS: El análisis representó 1316867 niños; 25% de madres urbanas y 37,5% de rurales que llevaron a sus hijos para atención preventiva. Variables asociadas con atención preventiva regular: niños <12 meses, bajo peso al nacer, antecedentes de enfermedades infecciosas, madre >35 años, escolaridad licenciatura, ama de casa, asistencia a >7 visitas de atención prenatal y vivienda en zona rural. 12% acudió a servicios de urgencias, 5,4% fueron hospitalizados y 66% recibió atención ambulatoria. Antecedentes de enfermedades infecciosas, madre que vive con su esposo o pareja, escolaridad licenciatura, asistencia a >7 visitas prenatales y tener un trabajo remunerado se asociaron con la utilización de servicios curativos. CONCLUSIÓN: Es indispensable fomentar que las madres lleven a sus hijos regularmente a atención preventiva.